Archaeometric Studies on the Characterization and Deteriorations of Glass Artifacts of Su Terazisi and Kral Kizi Regions in Enez (Ainos) Excavation - Buyuksoy, Didem Colak; Akyol, Ali Akin; Kocabas, Isil Ozsait (ISTANBUL UNIV, RESEARCH INST TURKOLOGY, DEPT ART HISTORY, 2021)
Archaeometric investigations were carried out to determine and correlate the chemical contents with the layers of deterioration of the 19 glass finds dating to the Roman Period uncovered from Su Terazisi and Kral Kizi Regions of Enez (Ainos) ancient city. The physical condition of glass finds was firstly examined, the layers of deterioration on the glass surface were documented with photographs, their thickness was measured with a digital thickness meter, their colors were identified by a chromameter, and images of the bubbles and deterioration products were taken under an optical microscope. When the deterioration layers of the samples belonging to the Roman Period were examined visually and with an optical microscope, the types of deterioration resulting from the chemical composition of the glass, such as iridescence, dulling, black discoloration and pitting were identified. A table was created of the existing degree of deterioration. Micro-XRF and Polarized Energy Dispersive-X-Ray Fluorescence (PED-XRF), Scanning Electron Microscope-Energy Dispersive Spectrometry (SEM-EDS), and Raman (Confocal) Spectroscopy methods were used to determine the element and mineralogical contents, and the deterioration layer of the glass samples. When all the archaeometric results were evaluated, it was revealed that there was a difference between the bulk glass and the deterioration layers.
Keywords: Archaeological Glass Chemistry; Archaeological Glass Deteriorations; PED-XRF; SEM-EDS; Raman Spectroscopy; ARCHAEOLOGICAL GLASS; ROMAN GLASS; CORROSION; BYZANTINE; MARINE; Art